Equipment for Dynamic Electron Contact Thermography of Skin Melanoma - Biloshenko, V.; Doroshev, V.; Karnachov, O.; Kutsenko, I.; Sluzhbin, Yu. (Science and Innovation, 2024)
The computer-assisted hardware complex for dynamic electron contact thermography of skin melanoma has been developed. A cooling device based on the Peltier cell, a matrix scanner with intellectual «temperature/digital code» converters, and an original customized software for visualizing and processing temperature maps have been created. The combined use of the complex and the dermatoscopy technique have been experimentally established to improve the validity of early diagnostics of skin melanoma.